Whey-derived valuable products obtained by microbial fermentation - Pescuma, Micaela (2015)
Whey, the main by-product of the cheese industry, is considered as an important pollutant due to its high chemical and biological oxygen demand. Whey, often considered as waste, has high nutritional value and can be used to obtain value-added products, although some of them need expensive enzymatic synthesis. An economical alternative to transform whey into valuable products is through bacterial or yeast fermentations and by accumulation during algae growth. Fermentative processes can be applied either to produce individual compounds or to formulate new foods and beverages. In the first case, a considerable amount of research has been directed to obtain biofuels able to replace those derived from petrol. In addition, the possibility of replacing petrol-derived plastics by biodegradable polymers synthesized during bacterial fermentation of whey has been sought. Further, the ability of different organisms to produce metabolites commonly used in the food and pharmaceutical industries (i.e., lactic acid, lactobionic acid, polysaccharides, etc.) using whey as growth substrate has been studied. On the other hand, new low-cost functional whey-based foods and beverages leveraging the high nutritional quality of whey have been formulated, highlighting the health-promoting effects of fermented whey-derived products. This review aims to gather the multiple uses of whey as sustainable raw material for the production of individual compounds, foods, and beverages by microbial fermentation. This is the first work to give an overview on the microbial transformation of whey as raw material into a large repertoire of industrially relevant foods and products.